Serbia: Criminal Law of the Republic of Serbia - Bugarski, Tatjana (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
The criminal legislation of the Republic of Serbia has a legal tradition of nearly a century. Moving through its development, today, it is at the level of modern criminal justice systems, which is largely in line with generally accepted international legal standards that ensure effective legislation while protecting and ensuring basic human rights. Intensive reforms of criminal legislation in the Republic of Serbia started at the beginning of the 21st century. Although legislative interventions in the field of criminal law have been highly intensive both quantitatively and qualitatively over the last two decades, it must be stated that the same trend is noticeable in other European countries, even those that traditionally have stable criminal legislation. The development of criminal legislation is, on the one hand, conditioned by the harmonization of criminal legislation with the law and standards of the European Union, while, on the other hand, the legislature is guided by other reasons because regardless of how much one strives for stable criminal legislation, one cannot deny the dynamic character of crime, the intensity of which is accompanied by social, political, economic, and other changes that have accelerated in the modern world. The paper presents an overview of the criminal legislation of the Republic of Serbia regarding the following issues: a brief history of its development, the primary legal sources, relevant institutions, and a comparison with relevant EU documents and key international trends. KEYWORDS: Republic of Serbia, relevant institutions of criminal justice, criminal law. criminal procedure law, execution of criminal sanctions